The role of buyer–supplier relationships in achieving economic sustainability in the private telecommunication sector in Zimbabwe - Tinotenda Fredrick Munyimi (Taylor & Francis Group, 2018)
This research assessed the role of buyer–supplier relationships in achieving economic sustainability in the private telecommunication sector in Zimbabwe. The objective was to determine the role of buyer–supplier relationships in achieving economic sustainability in the private telecommunication sector in Zimbabwe. The target population of this research was composed of private telecommunication companies in Zimbabwe. This study employed simple random sampling technique where a sample size of 76 procurement staff was selected to participate in this research as respondents; these were procurement managers, procurement officers, buyers and procurement clerks. The independent variables for buyer–supplier relationships were transactional types of relationships, collaborative relationships and strategic alliances relationships. On the other hand, the dependent variable was economic sustainability of private telecommunication companies in Zimbabwe. This study was a survey of private telecommunication companies in Zimbabwe and primary data were gathered by the use of self administered closed-ended questionnaires and open-ended interviews as research instruments. Data were analysed using descriptive and inferential statistics using Statistical Package Social Science (SPSS) software (Version 20), and quantitative results were presented in the form of tables. Analysis for variant ANOVA and multiple regression analysis were used to test the hypothesis. This research discovered that strategic alliance types of relationships with strategic suppliers and transactional relationships with suppliers of routine materials have a great role in achieving economic sustainability of private telecommunication companies in Zimbabwe; hence, this research recommends private telecommunication companies to partner with suppliers who supply strategic items and take advantage of transactional kind of relationships especially with those suppliers who supply routine items in order to take advantage of best available price in the market. Future research works are recommended to include the following: Would the recommendations for these kinds of relationships reduce corruptions dramatically or eliminate them?. This is because the current “Zimbabwe is open for business mantra” and telecommunication companies are promoting transparency in all activities which include procurement as part of their efforts to fight against corruption. Moreover, further research should be undertaken to find out why collaborative types of relationships such as closer–tactical and single sourced do not have a statistically significant role in achieving economic sustainability in the private telecommunication sector in Zimbabwe, despite the fact that previous literature is suggesting otherwise.